NECESSIDADES PSICOLÓGICAS BÁSICAS E A MOTIVAÇÃO NO AMBIENTE ESPORTIVO DE ATLETAS DE ATLETISMO E GINÁSTICA ARTÍSTICA - Adan Medina Ramires (2023)
Introduction: Motivation is a process by which human behavior is encouraged and energized to achieve objectives. According to Self-Determination Theory, the individual is a dynamic organism that moves to nurture three basic psychological needs (NPB) innate to every human being (autonomy, competence and relationship). Studies observe motivational phenomena in the most varied sociocultural environments, however, there are few contexts that illustrate this as well as sport. Regardless of the competitive level, motivation will be the focus of attention. Parents also play a prominent role in the relationship with motivation to practice sports, being the first agents of socialization and influencers of their children's positive and negative attitudes. There is evidence of parental influence in supporting NPB at different competitive levels. Objective: To analyze the perception of Brazilian athletes in the sports disciplines of Athletics (AT) and Artistic Gymnastics (GA), regarding basic psychological needs, motivation in sport and parental motivation. Methods: In the cross-sectional and quantitative study, carried out with 55 male and female athletes from Athletics (n= 24) and Artistic Gymnastics (n= 31), the Basic Needs Satisfaction Scale in Sport questionnaires were applied - BNSSS, Sports Motivation Scale – SMS II and the Motivational Climate Perceived by Parents – PIMCQ-2P, all in a virtual environment through the Medalha Project website. In statistics, the Shapiro-Wilk test was performed to verify data normality, descriptive analysis (M±SD) and variance analysis - ANCOVA (p≤0.05). Results and Discussion: Regarding NPB, satisfactory levels of support for the dimensions of Autonomy, Competence and Relationship were observed in all athletes. Regarding motivation in sport, in AT for both sexes and in GA for females, athletes demonstrated to be more intrinsically motivated. In the athlete's perception of the mother's and father's parental motivation, athletes from both sports perceived motivation more intrinsically as well. In comparisons, significant differences in NPB were observed only in the comparison between sports, in which AT athletes presented more Autonomy (p=0.03) in relation to GA athletes. Significant differences were found in motivation in sport only in the comparison between competitive categories, in which athletes in the youth category showed more Demotivation (p=0.01), and finally, significant differences in parental motivation only in the comparison between competitive categories, where athletes in the children's category perceived more motivation for Pleasure in Learning (p=0.01) and athletes in the youth category perceived more motivation with Emphasis on Error (p=0.02). Final considerations: Research can be a useful tool for a greater understanding of the factors that can enhance or attenuate athletes' desire to remain in their sports. Furthermore, it can help clubs, coaches and parents/guardians to reflect on creating an environment more conducive to the satisfaction of NPB, assisting in the universal growth and personal and social development of athletes. Keywords: Psychological needs. Sports motivation. Parental motivation.